Kinerja Reproduksi Induk Sapi Potong pada Usaha Peternakan Rakyat di Kecamatan Mojogedang - Joko Riyanto; Lutojo Lutojo; D. M. Barcelona (Universitas Sebelas Maret (UNS), 2015)
This study aims to determine of the reproductive performance of beef cows consists are Simpocow, Limpo cow and PO cow reared on the livestock. The research was conducted by survey on beefcattle 60 head in the District Mojogedang, Central Java Province from December 2014 throughFebruary 2015. The research parameter is post partum estrus (PPE), post partum mating (PPM),service per conception ( S / C), days open (DO). Results of the study were analyzed descriptively.Reproductive performance of Simpo cow, Limpo cow and PO cow are consecutive PPE: 3:56 ± 0.73months, 3.93 ± 0:40 months, and 6.75 ± 4.68 months, PPM: 3.85 ± 0.70 months, 3.79 ± 0:51 months,and 4:42 ± 1.23 months, S / C: 1.45 ± 0:20 times, 1.74 ± 0:07 time, and 1:38 ± 0:38 times, DO: 5:33 ±0:58 months, 8:44 ± 4.65 months, and 9:27 ± 5.93 months, CI: 14:33 ± 0:58 months, 14:44 ± 0.66months, and 14:44 ± 0.66 months. The conclusion shows that the reproductive performance of theSimpo cow, Limpo cow and PO cow in District Mojogedang appears that the value of post-partumestrus (PPE) and post partum mating (PPM) is panjang.Service per conception (S / C) is high. Daysopen (DO) and calving interval (CI) are both still long.